Using targeted short‐term field investigations to calibrate and evaluate the structure of a hydrological model. Issue 5 (7th May 2013) - Hughes, D. A.; Gush, M.; Tanner, J.; Dye, P.
Abstract This study combines the application of a hydrological model with the use of field data derived from short period measurement campaigns at two sites, one a low topography forested area and the other a steep grassland catchment. The main objective was to determine if the structure of the widely used Pitman model could be considered appropriate for simulating the field data. The model is typically applied at coarse spatial and temporal (1 month) scales, while the tests reported here use data from small catchments and are applied in a daily version of the model. The results demonstrate the importance of ensuring that field observations are measuring the same hydrological variables as the model simulations. At one study site, there was a mismatch in the soil moisture data that was corrected by incorporating a two‐layer soil algorithm into the model. The model results from both field sites identified the sensitivity of the model to assumptions about evaporative demands and indicate that the model structure is very sensitive to the potential evaporation inputs. The overall conclusion is that the model structure is generally appropriate for simulating the hydrological responses at the two sites, but that there remain some unresolved uncertainties about specific model components and the use of certain types of input data. The study lends support for the future development of a more complete daily version of this widely used model. Copyright © 2013 John Wiley & Sons, Ltd.